2020
DOI: 10.1017/s1092852920001303
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution and mental health: a narrative review of literature

Abstract: Pollutant agents are exponentially increasing in modern society since industrialization processes and technology are being developed worldwide. Impact of pollution on public health is well known but little has been described on the association between environmental pollutants and mental health. A literature search on PubMed and EMBASE has been conducted and 134 articles published on the issue of pollution and mental health have been included, cited, reviewed, and summarized. Emerging evidences have been collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 118 publications
0
26
0
6
Order By: Relevance
“…Green spaces and access to blue spaces (sea, rivers, and lakes) are significantly associated to better self-perceived mental health as well as pollution and noise are related to higher prevalence of mental disorders due to direct neurotoxicity or indirect psychological stress. [16][17][18] This narrative mini-review aims to provide an up-to-date report on the emerging mental health issues in the urban settings and possible risk factors involved in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Green spaces and access to blue spaces (sea, rivers, and lakes) are significantly associated to better self-perceived mental health as well as pollution and noise are related to higher prevalence of mental disorders due to direct neurotoxicity or indirect psychological stress. [16][17][18] This narrative mini-review aims to provide an up-to-date report on the emerging mental health issues in the urban settings and possible risk factors involved in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…hyperactivity and/or inattention at age 15). A subsequent narrative review of 134 articles relating to pollution and mental health by Ventriglio and colleagues [ 15 ] similarly included little on adolescent mental health. The review, which was not systematic, reported neurodevelopmental disorders (including ADHD and ASD) and cognitive deficits among children (generally younger than 10) exposed to air, light, or noise pollution; heavy metals; and/or pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…The review, which was not systematic, reported neurodevelopmental disorders (including ADHD and ASD) and cognitive deficits among children (generally younger than 10) exposed to air, light, or noise pollution; heavy metals; and/or pesticides. This review made little reference to mental illness that was not neurodevelopmental (such as depression or anxiety) [ 15 ]. There was a single mention of increased ‘psychiatric conditions’ following children’s exposure to ultrafine particles and one of ‘a mental disorder’ following a 16-year-old female’s exposure to mercury.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, os resíduos e seus produtos de degradação deixados nos alimentos podem exercer efeitos prejudiciais sobre o sistema nervoso (Xie et al, 2020;Ventriglio et al, 2021;Kaushal et al, 2021;Poirier et al, 2021), reprodutivo…”
Section: Uso De Agrotóxicos Em áReas De Proteção Ambientalunclassified
“…Anualmente no mundo ocorrem mais de 300.000 mortes atribuídas a organofosforados e cerca de 1 milhão de intoxicações não intencionais e 2 milhões intencionais (Dodson et al, 2021). Os agrotóxicos podem não produzir efeitos de forma aguda e por isso serem classificados como medianamente ou pouco tóxicos, mas devemos considerar os efeitos crônicos ou até transgeracionais, causando várias doenças como cânceres, malformação congênita, distúrbios endócrinos, neurológicos e mentais (Bergman et al, 2013;Armiliato, 2014;Carneiro, 2015;Ventriglio et al, 2021).…”
Section: Efeitos Dos Agrotóxicos Nos Organismosunclassified